Combating Climate Change with Green Central Banking: A Continuous-Time, Stock-Flow Consistent Approach - Milic, Luka (My University, 2021)
Climate change is one of the biggest threats humanity has ever confronted as it threatens both environmental and financial stability. Therefore, this thesis aims to add to the current literature surrounding stock-flow consistent continuous-time climate-economy models by exploring the role of innovative green debt instruments, such as green bonds and green loans, in aiding the private sectors' transition towards net-zero emissions. Moreover, the increased financialization of the macroeconomic system opens up the opportunity to explore unique climate-related monetary policies such as green quantitative easing (QE) and a green interest rate and whether they alleviate short-term debt burdens without neglecting the long-term destabilizing effects of climate change. Our key findings include: (i) providing the productive sector with a more efficient alternative to financing mitigation costs via green fixed-income resulted in increased debt levels that the central bank is ill-equipped to reduce; (ii) introducing green loans as a financial avenue towards renewable energies increased the effectiveness of monetary intervention as the green interest rate served its dual purpose of reducing short-term debt burdens, promoting a faster reduction of carbon emissions and minimizing the long-term destabilizing effects of climate change.